New Educational Technologies to Develop Foreign Language Communicative Competence of Non-Linguistic Students: Digital Storytelling (Филологический класс, 2021)
The paper discusses the issue of introduction of new educational technologies as a tool for developing students’ communicative competence in foreign language learning. The study is aimed at analyzing the impact of digital story creation in a foreign language on the development of students’ foreign language communicative competence, their motivation to learn a foreign language and their adaptation to academic environment. Review of literature on readiness of modern higher education to wide implementation of e-learning components is given; reasons preventing their introduction into teaching of foreign languages are described. Analysis of implementing digital storytelling in a foreign language teaching is presented. The impact of the first-year students’ participation in creation of digital stories on their language learning motivation and adaptation to university environment is considered. The data, collected from surveys and digital stories, created by students and assessed by university teaching staff, were analyzed. The results prove a positive impact of digital storytelling educational technology on students’ motivation in foreign language learning, as well as on the process of first-year students’ adaptation to academic environment. The results also demonstrate that creation of digital stories contributes to formation and development of variety of learners competences, including foreign language communicative competence and helps improve students’ soft skills. The contribution of each author in this research is the following: E. Makarova – 50% (theoretical background of the problem and approbation), I. Pirozhkova – 50% (methodology, approbation and results analysis).